An indirect competitive ELISA for determination of guanidine acetic acid in animal feed - Xingdong Yang; Lili Li; Yang Qu; Lihua Wu; Chenchen Wang; Beibei He; Zhenchun Zang; Xiaofei Hu (Scientific Reports)
Abstract To establish an indirect competitive ELISA (ci-ELISA) for the detection of guanidino acetic acid (GAA) residues in animal feed, in this study, GAA was coupled to carrier proteins via the active ester method to obtain an anti-GAA complete antigen (GAA-BSA) and a detection antigen (GAA-OVA). BALB/c mice were immunized with GAA-BSA, after which anti-GAA monoclonal antibodies were prepared via hybridoma and other techniques. An ic-ELISA method was developed by optimizing the reaction conditions and the accuracy, precision and specificity of the method were determined. The results showed that GAA was successfully coupled to the carrier protein; a hybridoma cell line (2C4) against GAA was obtained, and the IC50 value of the monoclonal antibody was 4.65 µg/kg; The average recovery rate of GAA spiked in animal feed by this method was 87.4%, and its intra-assay coefficients of variation were greater than the inter-assay coefficients of variation in all assays; no cross-reaction with the other competing reactants was detected. The indirect competitive ELISA method developed in this study was able to fulfil the requirements for the determination of GAA r esidues in animal feed.